Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Answer this Question


Answer This Question class=

Sagot :

tmcss

Answer:

n = -13

Step-by-step explanation:

√10 - 3n = 7 ⇔

⇔ 10 - 3n = 49 ⇔ We need to remove the square root. Ex: √n = 2 ⇔ n = 2²

⇔  -3n = 49 - 10 ⇔
⇔ -3n = 39 ⇔
⇔ n = [tex]\frac{39}{-3}[/tex] = -13 (as -3 changes members, as it was multiplying, it now divides, conversion).